PARENTAL COMMUNICATION PATTERNS IN SHAPING ADOLESCENTS' BEHAVIOR ON MOM'SCORNER CONTENT ON NIKITA WILLY'S YOUTUBE - Fahriah, Hasna; Tanjung, Hasan Basri; Dewi, Reni Sinta (Al-Mubin, 2025)
Applicable and inspirational parental communication practices start from proper communication patterns and parenting, especially between parents and adolescents. In the midst of digital flow, social media is placed as a means of learning and education that is quite capable and attracts a lot of interest from the public, especially parents in learning family communication. This is a reference for researchers to find out more about communication between parents and adolescents. This study aims to analyze what kind of communication patterns parents use in shaping adolescent behavior on #mom'scorner content on YouTube Nikita Willy episode 39. This study uses a qualitative method of library research method with a type of content analysis. Data was collected through podcast video documentation and analyzed using communication and parenting pattern theory. The results of the study show that (1) the assertive communication pattern is the communication pattern that is considered the most effective in prioritizing honesty, openness, and empathetic attitude shown by parents to children, but still providing appropriate direction and clear limits to children, (2) there are factors that affect the effectiveness of parental communication patterns. Starting from parents' understanding of children's psychological needs such as love, security, value, and opportunities provided by parents. In addition, the influence of the social environment such as extended family, friends, neighbors, community and even social media. Therefore, the pattern of assertive communication is the right reference in forming good behavior in adolescents